Developing digital lessons to integrate social science teaching in Colombia using Google Earth. Issue 2 (5th May 2021) - Mejía Ávila, Doris; Sánchez Agámez, Carlos; Soto Barrera, Viviana Cecilia
Abstract: A pilot test for the design and construction of digital lessons for integrated social science teaching is presented in this study. Combing conventional texts, applications made with Google Earth, and images from the web, three lessons for the sixth grade were created: (1) Evolution of Man, (2) Physical Geography of the Earth, and (3) Pre-Columbian America. Interactive workshops were held with a group of 60 teachers from the city of Montería, Colombia, to identify the strengths, weaknesses, opportunities, and threats that allowed for the construction of a SWOT matrix. SWOT analysis allowed for the identification of educational limitations in Montería resulting from limited classroom access to computers and the internet and the insufficient teacher knowledge regarding information technology and geotechnologies. This analysis also allowed for the identification of guidelines for the development of digital lessons. These lessons serve as a methodological proposal for teaching social science, promoting the integration of such topics as geography, history, and environmental science. This integrative method motivated the teachers, who believed that it could be a path to true integration of the social sciences.